Heterologous Expression of the Hypovirus Chv1-Ep713 Full-Length Cdna in Botrytis Cinerea: Transformation with Agrobacterium Tumefaciens and Evaluation of Changes in the Fungal Phenotype - Armijo-Godoy, G (BioMed Central Ltd, 2025)
Background: Botrytis cinerea is a phytopathogenic fungus responsible for gray mold disease in a wide range of hosts, including ornamentals, vegetables, and fruit-bearing plants. Similarly, Cryphonectria parasitica infects the American chestnut, causing a lethal condition known as chestnut blight. From this species, the CHV1-EP713 virus, classified as a hypovirus due to its ability to reduce fungal virulence, has been isolated and characterized. Building on this knowledge, we aimed to express the full-length cDNA of CHV1-EP713 in B. cinerea to asess whether its expression could alter the fungal phenotype. Results: To achieve the expression of the hypovirus cDNA in B. cinerea, the pXH9 vector encoding the CHV1-EP713 cDNA and the p18 plasmid containing the Agrobacterium tumefaciens Ti plasmid T-DNA region were fused to generate the p18-XH9 construct. Transformation of the virulent B. cinerea strain CCg55L with A. tumefaciens carrying this construct yielded hygromycin B-resistant transformants. Nucleic acid analysis revealed a ~ 13-kbp double-stranded RNA, consistent with a replicative intermediate of the viral genome. PCR and RT-PCR confirmed integration and expression of the viral cDNA, supporting the establishment of a productive mycoviral infection. Phenotypically, transformants showed reduced radial growth and sporulation compared to the parental strain. Moreover, grapevine leaf infection assays revealed significantly reduced tissue damage and distinct oxidative responses, indicating a reduction in virulence. Conclusion: Together, these results demonstrate that transformation of a virulent B. cinerea strain with CHV1-EP713 cDNA can lead to phenotypic changes consistent with hypovirulence. The observed alterations in growth, sporulation, and pathogenicity are likely linked to viral expression and/or replication, highlighting the potential of hypoviruses as biological control agents against phytopathogenic fungi. © The Author(s) 2025.